Investigation of target dose conformity using normoxic polymer gel dosimetry techniques: A clinical example of 12th thoracic vertebrae SBRT treatment with VMAT. Issue 1 (1st January 2022) - Venning, A; Mundayadan Chandroth, M; Morgan, C; Roberts, M
Abstract: This paper describes the 3D dosimetry verification of a 24Gy in 3 fractions VMAT SBRT treatment delivery to the 12 th thoracic vertebrae (T12). With this fractionation regime, the critical isodose value is 17.5Gy to the outer edge of the spinal cord and must not be exceeded. This is a high-risk treatment that could result in severe injury to the patient unless administered precisely. With the use of 3D normoxic polymer gel dosimetry techniques, using MRI readout, a clinical example is presented which shows that the Mid North Coast Cancer Institute's paraspinal program is capable of delivering complex distributions with high doses to within very tight tolerances. This also demonstrates the strength of normoxic polymer gel as a 3D dosimeter.